Maryna Romanivna Cherkashіna-Gubarenko: universalism of creative personality - Vira, Artemieva (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The diverse professional activity of Marуna CherkashinaGubarenko is analyzed for the first time in Ukrainian musicology in terms of the relationship between the personal factors of the musicologist's activity and modern concepts of the phenomenon of activity universalism. The main objective of the study to reveal the specifics of the phenomenon of universalism of the creative personality of Marуna Cherkashina-Gubarenko. The methodology includes historiographical, biographical, phenomenological, and culturological methods that create conceptual guidelines for understanding the essence of the phenomenon of the universal creative personality of Marуna Cherkashina-Gubarenko. Results and conclusions. The phenomenon of a universal creative personality in its general sense has attracted public attention since Antiquity to the present day. The considered types of activities of a universal creative personality are the main lines of embodiment of the diverse interests of M. Cherkashina-Gubarenko. Many years of her multi-vector activity in the field of Ukrainian musicology gives grounds to consider her as a "universal creative personality", which is characterized by a combination of at least three types of activities. Considering the importance of the creative component in the structure of the personality, we note that the manifestation of M. CherkashinaGubarenko in her work was partially realized in the field of librettology - she was the author of several libretti to operas and wrote poems. In the professional sphere of M. Cherkashina-Gubarenko, three leading types of activity can be distinguished: musicology, music-social activity and music pedagogy. The musicologist had a long and powerful period of scientific and creative life, which amounted to about 60 years. The results of her musicological activity are presented in the form of several individual monographs, a textbook and collections of articles. In addition, M. CherkashinaGubarenko is the author of about 100 articles. The artist's interests covered a wide range of topics: from the trends in the development of Western European opera theater from the Baroque to the present day, the phenomenon of "director's opera" in the musical theater of the 20th–21st centuries to the traditions and features of modern Ukrainian musical culture. The most representative project of musical and public activity was the founding of the Kyiv Wagner Society by M. Cherkashina-Gubarenko in 1996. The results of the musicologist's activity as a talented teacher are more than 50 graduates, 34 candidates and 8 doctors of art history. Numerous researchers continue to work in the field of Ukrainian musicology, supporting the traditions of the scientific school of M. Cherkashina-Gubarenko.